Nozioni di base della lingua italiana per il settore del turismo - Kompara Lukančič, Mojca (University of Maribor Press, 2022)
1st supplemented edition. Basics of the Italian Language for the Field of Tourism. The professional monograph Basics of the Italian Language for the Field of Tourism – Second edition represents an excellent basis for all those who work in the field of tourism and use the Italian language. The monograph includes 5 sectors and 34 units, which offer the reader both theoretical notions and their application in the language of tourism. The reader has the opportunity to enrich their vocabulary thanks to the authentic texts of various subfields such as hotel, catering, tourist destinations, gastronomy and winemaking, wellness and selfness. Nevertheless, the topics discussed are not limited exclusively to the tourism field, but also include cultural concepts, which encompass multidisciplinary and multicultural points of view, providing the reader with a complete view of the basics of the Italian language for the field of tourism.